Remarks by World Bank Group President David Malpass to the Europe Institute at the University of Zurich - Malpass, David (World Bank, Washington, DC, 2022)
These remarks were delivered by World Bank Group President David Malpass to the Europe Institute at the University of Zurich. He discusses on: Churchill symposium; Ukraine, refugees, and fragility; energy realignment; inflation, debt, and growth; the challenge of global public goods; and Swiss partnership.